Efficacy of Aspirin in the Primary Prevention of Cardiovascular Diseases and Cancer in the Elderly: A Population-Based Cohort Study in Korea - Jung, Minji; Lee, Sukhyang (Drugs and Aging, 2020)
Introduction: Aspirin is widely used to prevent cardiovascular diseases (CVDs). However, the balance of its benefits and risks in the primary prevention of CVDs and cancer is unclear, especially in elderly Asians. The present study aimed to evaluate the efficacy of aspirin in the primary prevention of major adverse cardiac and cerebrovascular events (MACCE), bleeding risk, and cancer in elderly Koreans with cardiovascular (CV) risk factors. Methods: This retrospective cohort study used data from the Korean National Health Insurance Service–Senior cohort database (2002–2015). Patients aged 60–90 years with hypertension, type 2 diabetes mellitus (T2DM), or dyslipidemia were identified. Aspirin users were compared with non-users using propensity score matching at a 1:3 ratio. The primary outcome was MACCE, a composite of CV mortality, myocardial infarction, and ischemic stroke. The secondary outcomes were the components of MACCE, all-cause mortality, angina pectoris, heart failure, the incidence and mortality of cancer, and the risks of hemorrhagic stroke and gastrointestinal bleeding. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using a Cox proportional hazard model. Results: A total of 3366 aspirin users and 10,089 non-users were finally included in the study. During a mean follow-up of 7.8 years, the incidence of MACCE was 15.2% in aspirin users and 22.4% in non-users. The risk of MACCE was significantly lower in aspirin users than in non-users (HR 0.76; 95% CI 0.69–0.85), and this risk was significantly reduced in patients using aspirin over 5 years (HR 0.52; 95% CI 0.46–0.60). Aspirin use was associated with a 21% reduction in the risk of primary cancer (HR 0.79; 95% CI 0.70–0.88) and cancer-related mortality (HR 0.72; 95% CI 0.61–0.84). No significant differences in bleeding risks were observed between the two groups. Conclusion: Aspirin reduced the risks of MACCE and cancer without increasing the bleeding risk in elderly Koreans with hypertension, T2DM, or dyslipidemia. Moreover, the benefits of the long-term use of aspirin in reducing the risks of MACCE were demonstrated. However, the decision of using aspirin for primary prevention must be carefully made on an individual basis, while estimating the benefit–risk balance of aspirin.
Keywords: Aged; Aged, 80 and over; Aspirin; Cardiovascular Diseases; Cohort Studies; Diabetes Mellitus, Type 2; Dyslipidemias; Female; Hemorrhage; Humans; Hypertension; Incidence; Male; Middle Aged; Neoplasms; Primary Prevention; Proportional Hazards Models; Republic of Korea; Retrospective Studies; Risk Assessment